Апроксимація дистрибутивної функції відбивної здатності поверхні поліном третього степеня - Романюк, О. Н.; Снігур, А. В.; Романюк, О. В.; Коваль, Л. Г.; Завальнюк, Є. К. (Vinnytsia National Technical University, 2023)
In the article a bidirectional reflectance distribution function based on a polynomial of the third degree is developed. The main disadvantages of Schlick, Phong, Blinn reflectance models are analyzed. The approximation of Blinn-Phong model by a cubic polynomial is proposed to improve the productivity of three-dimensional image formation. Formulas for the coefficients of the approximation cubic polynomial are calculated. The disadvantages of using the proposed cubic polynomial for reproducing the glare’s attenuation zone are considered. A function for high-precision reproduction of this zone is proposed, formulas of its coefficients are calculated. A combined function, combining a cubic polynomial for reproducing the glare’s epicenter zone and a function for reproducing the attenuation zone, is proposed. The plot of the combined function is built. It is shown that the combined function reproduces the glare’s epicenter and attenuation zones with small relative and absolute errors. The developed reflectance model provides a highly-productive formation of three-dimensional scenes in computer graphics systems. The proposed distribution function of surface reflectivity can be used in computer graphics systems.